Safety and efficacy of biliary stenting combined with iodine-125 seed strand followed by hepatic artery infusion chemotherapy plus lenvatinib with PD-1 inhibitor for the treatment of extrahepatic cholangiocarcinoma with malignant obstructive jaundice - Lin, Long-Wang; Ke, Kun; Chen, Rong; Yang, Wei-Zhu; Huang, Ning; Wu, Zheng-Zhong (Frontiers in Immunology, 2024)
Objectives To evaluate the efficacy and safety of biliary stenting implantation with iodine-125 seed strand (SI) followed by hepatic artery infusion chemotherapy (HAIC) plus lenvatinib (Len) with programmed death-1 (PD-1) inhibitor for patients diagnosed with extrahepatic cholangiocarcinoma (ECC) and malignant obstructive jaundice (MOJ). Methods In this single-center retrospective study, the data of ECC patients with MOJ from March 2015 to January 2023 was assessed. Using probability score matching (PSM), the selection bias of patients was reduced. Primary study outcomes included overall survival (OS) and progression-free survival (PFS). The OS and PFS were performed using the Kaplan–Meier method and evaluated with the log-rank test. Results A total of 104 patients were enrolled finally, including 52 patients treated with interventional therapy (SI+HAIC) plus Len with PD-1 inhibitor (SI+HAIC+Len+P group) and 52 patients treated with interventional therapy (SI+HAIC) plus lenvatinib (SI+HAIC+Len group). 26 pairs of patients were matched after PSM analysis. After PSM analysis, the median OS and PFS in the SI+HAIC+Len+P group were significantly longer compared to those in the SI+HAIC+Len group (OS:16.6 vs. 12.3 months, P = 0.001; PFS:12.6 vs 8.5 months, P = 0.004). The DCR was significantly different between groups (P = 0.039), while ORR not (P = 0.548). The addition of PD-1 inhibitor was generally well tolerated without treatment-associated mortality. Conclusion Interventional therapy (SI+HAIC) plus Len with PD-1 inhibitor was effective for ECC patients accompanied by MOJ with a manageable safety profile.